2017
DOI: 10.29311/mas.v15i1.663
|View full text |Cite
|
Sign up to set email alerts
|

‘We are… we are everything’: the politics of recognition and misrecognition at immigration museums

Abstract: Qualitative interviews were undertaken with visitors at five museums that display the histories and experiences of immigration in the United States and Australia. This paper outlines the range of embodied performative practices of meaning making that visitors undertook during their visits and the meanings and political values that they created or reaffirmed in doing so. The key performance at these museums were the affirmation and reinforcement of familial, ethnic and national identities in which individuals e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This may in fact compete with more forward-looking and inclusive notions so that the term community can mean different things to different people at the same heritage site. Laurajane Smith s crossnational empirical work in heritage studies confirms this (Smith 2017;Smith 2019). Her visitors to various labour history sites and museums in the US, Australia and the UK all took community as a positive term yet meant quite different things by it, largely based on their preexisting values and politics.…”
Section: The (Largely Left-wing) Uses Of Community In Anglophone Research On Heritagementioning
confidence: 87%
“…This may in fact compete with more forward-looking and inclusive notions so that the term community can mean different things to different people at the same heritage site. Laurajane Smith s crossnational empirical work in heritage studies confirms this (Smith 2017;Smith 2019). Her visitors to various labour history sites and museums in the US, Australia and the UK all took community as a positive term yet meant quite different things by it, largely based on their preexisting values and politics.…”
Section: The (Largely Left-wing) Uses Of Community In Anglophone Research On Heritagementioning
confidence: 87%
“…Misrecognition was often framed as a cultural and institutional process of disrespect, stigmatisation, and denigration that devalued some people compared to others (the dominant ethnic and/or socioeconomic groups within a society) [197][198][199][200]. In the context of Indigenous communities, misrecognition included the general disrespect for Indigenous groups' cultural identities, values and knowledge systems (#3, #9, #18, #22, #26, #33), as well as Indigenous ways of living more broadly [85,191,192].…”
Section: Recognitional Injusticementioning
confidence: 99%
“…They found that white middle/elite classes' cultural symbols spoke for national heritage experience, and white middle/elite classes' history were prioritized over that of others, such as black, ethnic, and feminine, in Britain. Smith (2017) draws on Fraser's recognition principle in her study of five museums that exhibit immigrants' histories and experiences in the U.S. and Australia [29]. She found that misrecognition was being cultivated through the representations that facilitated marginalization and injustice towards the immigrants (see also [30]).…”
Section: Recognitionmentioning
confidence: 99%